DEVELOPMENT OF HIGHBUSH BLUEBERRY (Vaccinium corymbosum hort. non L.) in vitro SHOOT CULTURES UNDER THE INFLUENCE OF MELATONIN - Wojciech Litwińczuk; Magdalena Wadas-Boroń (Acta Scientiarum Polonorum: Hortorum Cultus, 2009)
The influence of melatonin (MEL) in comparison with IAA, IBA (all at 5.71 μM), and auxin-free (0) medium on development of highbush blueberry (Vaccinium corymbosum hort. non L.) ‘Herbert’ in vitro shoot cultures was examined. Depending on the kind of hormone in vitro cultures consisted of various number of axillary (AX) and adventitious (AD) shoots. The influence of melatonin on in vitro cultures was intermediate but more similar to IAA than IBA. Production of axillary shoots on media supplemented with MEL and IAA was comparable and higher than on medium with IBA. In contrast to IAA melatonin reduced development of adventitious shoots. Contrary to IBA-obtained cultures AX shoots grown on ‘IAA’, ‘0’, and ‘MEL’ media resembled AD shoots.